Survival Vocabulary of Wuna Language in Plant Environment of Kowala - Ode Sidu, La; Niampe, La; Ino, La (International Research Journal of Management, IT & Social Sciences, 2016)
This article is taken from the results of a study entitled "Survival Vocabulary of Wuna Language in Plant Environment of Kowala ". The purpose of a study is to describe and analyze the survival vocabulary of Wuna Language in the plant environment kowala. The method used the field method. In presenting the data used quantitative descriptive method and data analysis used in the study method. Based on the analysis of data, amongst the 200 vocabularies submitted to 50 respondents, showed that most of the vocabulary in the plant environment kowala still significant in surviving. Plant kowala still closely related to communityâs lives in the areas of social, economic, moral ethics and faith. Furthermore, community attitudes toward kowala plants still appreciate it. This can be showed by their attitude to let the plants of kowala grow anywhere, as shown in communitys gardens, in the middle of the plant teak, guava or anywhere without any interference from the community.